Recirculation in Extracorporeal Membrane Oxygenation: The Warning Comes From the Cannula. Issue 8 (August 2021) - Descamps, Richard; Mombrun, Martin; Valette, Xavier; Du Cheyron, Damien
Abstract : Supplemental Digital Content is available in the text.